Field to palette dialogues on soil and art in the Anthropocene - Toland, Alexandra R. 1975-; Noller, Jay Stratton; Wessolek, Gerd 1953- (CRC Press, Taylor & Francis Group, 2019)
Respect for and conservation of soil, as a growing medium and as an artists' material
Includes bibliographical references
Keywords: Soil conservation; Soil management; Artists' materials; Kunst; Bodennutzung; Boden; Bodenschutz; Aufsatzsammlung